2022
DOI: 10.1038/s41598-022-24198-2
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties and acoustic emission analysis of desert sand concrete reinforced with steel fiber

Abstract: In this study, to reduce the consumption of natural sand and improve the utilization rate of desert sand in western China, while preparing 14 groups of samples, desert sand is used to replace natural sand by the ratio of 20%, 40%, and 60%, and steel fiber is mixed with volume fraction 0.5%, 1.0%, 1.5%, and 2.0%. The mechanical properties of the specimens, including compressive strength, splitting tensile strength, and axial compressive strength were tested. Besides, the microstructures of the samples were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Volumetric fiber content up to 1.5% in HSC (V f ) generally increases compressive strength by about 10–20% compared to HSC without fibers 4 , 5 . There are also studies which show no effect of fibers on compressive strength, or even its reduction 6 9 . With increasing fiber content (V f ) in the composite, there is also an increase in the strain at maximum compressive stress 5 , 7 – 11 , while the effect of fiber addition on the rising part of the stress–strain curve (σ–ε) is small and clearly noticeable for the descending part of the σ–ε graph 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Volumetric fiber content up to 1.5% in HSC (V f ) generally increases compressive strength by about 10–20% compared to HSC without fibers 4 , 5 . There are also studies which show no effect of fibers on compressive strength, or even its reduction 6 9 . With increasing fiber content (V f ) in the composite, there is also an increase in the strain at maximum compressive stress 5 , 7 – 11 , while the effect of fiber addition on the rising part of the stress–strain curve (σ–ε) is small and clearly noticeable for the descending part of the σ–ε graph 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Fiber-reinforced concrete technology has been applied in DSC. Some researchers experimentally found that mixing steel fibers could substantially enhance the compressive strength and splitting tensile strength of DSC, and the enhancement of the latter strength was relatively obvious [ 42 , 43 , 44 ]. Steel fibers account for the most commonly used option in the current literature, yet they have the disadvantages of self-weighting and easy corrosion [ 45 ].…”
Section: Introductionmentioning
confidence: 99%